Comparison Between 5- and 1-Year Outcomes Using Cutoff Values of Pressure Drop Coefficient and Fractional Flow Reserve for Diagnosing Coronary Artery Diseases - Banerjee, Rupak K. (Front Physiol, 2021)
BACKGROUND: The current pressure-based coronary diagnostic index, fractional flow reserve (FFR), has a limited efficacy in the presence of microvascular disease (MVD). To overcome the limitations of FFR, the objective is to assess the recently introduced pressure drop coefficient (CDP), a fundamental fluid dynamics-based combined pressure–flow index. METHODS: We hypothesize that CDP will result in improved clinical outcomes in comparison to FFR. To test the hypothesis, chi-square test was performed to compare the percent major adverse cardiac events (%MACE) at 5 years between (a) FFR < 0.75 and CDP > 27.9 and (b) FFR < 0.80 and CDP > 25.4 groups using a prospective cohort study. Furthermore, Kaplan–Meier survival curves were compared between the FFR and CDP groups. The results were considered statistically significant for p < 0.05. The outcomes of the CDP arm were presumptive as clinical decision was solely based on the FFR. RESULTS: For the complete patient group, the %MACE in the CDP > 27.9 group (10 out of 35, 29%) was lower in comparison to the FFR < 0.75 group (11 out of 20, 55%), and the difference was near significant (p = 0.05). The survival analysis showed a significantly higher survival rate (p = 0.01) in the CDP > 27.9 group (n = 35) when compared to the FFR < 0.75 group (n = 20). The results remained similar for the FFR = 0.80 cutoff. The comparison of the 5-year MACE outcomes with the 1-year outcomes for the complete patient group showed similar trends, with a higher statistical significance for a longer follow-up period of 5 years. CONCLUSION: Based on the MACE and survival analysis outcomes, CDP could possibly be an alternate diagnostic index for decision-making in the cardiac catheterization laboratory. CLINICAL TRIAL REGISTRATION: www.ClinicalTrials.gov, identifier NCT01719016.